Legal Power of Buying and Selling Land on the Basis of Power of Sale Under Hand - Minarsih, Minarsih; Arifulloh, Achmad (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2025)
The purpose of this study is to analyze the legal force of sales and purchases carried out based on a power of attorney to sell underhand and to examine the judge's legal reasoning in deciding case Number 50/PDT.G/2023/PN Pekalongan. The problem arises because the practice of sales and purchases with a power of attorney to sell underhand is still widely carried out by the public, even though according to Indonesian positive law, the transfer of land rights must be carried out with an authentic deed by a Land Deed Making Officer (PPAT) as regulated in Article 37 paragraph (1) of Government Regulation Number 24 of 1997 concerning Land Registration. This research uses a normative legal research method with a statutory, conceptual and case study approach to the court decision. The results of the study indicate that a sale and purchase based on a power of attorney to sell underhand has limited legal force, because it is valid in civil law as long as it meets the requirements of Article 1320 of the Civil Code, but cannot give rise to material legal consequences in the form of transfer of land ownership rights. The agreement is obligatory (binding the parties), but not yet translatable (transferring rights). A private deed only has evidentiary force as long as it is acknowledged by the signing party and cannot be used as a basis for registering land rights at the land office. Based on an analysis of the judge's considerations, it was found that the legal reasoning used in the Pekalongan District Court decision did not fully reflect the ideal legal rationality as stated by Philipus M. Hadjon. The judge attempted to balance justice and legal certainty, but his legal considerations showed inconsistencies between civil norms and land administration norms. The judge emphasized casuistic justice more than formal legal certainty, so that the decision was substantively fair to the parties, but normatively had the potential to create legal uncertainty in the future. Thus, this study emphasizes the importance of the role of authentic deeds as an instrument of legal protection in land sale and purchase transactions, as well as the need for consistency in the judge's legal reasoning to align with the principles of legal certainty, justice, and benefit.